The Iraqi Woman in the Face of Climate Change: Challenges, Obstacles, and Empowerment Strategies (قضايا سياسية, 2024)
The research aimed to diagnose and analyze the factors that make Iraqi women more vulnerable to the effects of climate change compared to men, in addition to raising awareness of women's issues in this field. This is because their inclusion in the formulation of climate change policies and strategies has become a global issue and ranks high in achieving sustainable development goals. The researcher used a descriptive, analytical, and statistical approach to analyze the research topics. The research reached several conclusions, including that the more empowered women are, the more successful a state's strategic plans are. They are more willing to participate in climate change adaptation strategies, contributing to the sustainability of natural resources, water conservation, land reclamation, enriching international negotiations, and being part of the solution, on equal footing with men, either by their presence in Iraqi delegations participating in climate negotiations or through their participation in international forums related to the environment and climate change. The research recommended the integration of women into all national climate change policies, strategies, and measures, and learning from the experiences of some countries that have implemented this approach.